Dynamic Learning for the Arabic language - Muh Barid Nizarudin Wajdi (STAI Miftahul Ula Nganjuk, 2019)
The teaching of Arabic is very interesting to be studied in comprehensive. Not only because of its function and essence for the life of Islamic communication, but because of its nature that is in the midst of ongoing education traditions are in need of various innovations, as a logical consequence the development of science and technology. The development of science and technology that is so rapidly for human life, it is necessary to work on language teaching technicians. In addition to the above, more interesting, in the spotlight that has a criticism from experts and society to the ability of students or students, especially students of IAIN or STAIN against the Arabic language. From the existing phenomenon, many among Islamic education institutions in Indonesia, more leaving the impression of the importance of teaching grammar mastery alone, as seen in memorizing the rules of language. Consequently we will not be surprised that while there is one who is good at mastering the Arabic grammar, but weak in terms of the functioning of the Arabic language itself, as a language of communication. Therefore, in this paper we are trying to raise the theme of